Tissue Factor Noncoagulant Signaling: Mechanisms and Implications for Cell Migration and Apoptosis - Åberg, Mikael; Eriksson, Oskar; Siegbahn, Agneta (Seminars in Thrombosis and Hemostasis, 2015)
Tissue factor (TF) is a 47-kDa transmembrane glycoprotein and the main initiator of the blood coagulation cascade. Binding to its ligand factor VIIa (FVIIa) also initiates noncoagulant signaling with broad biological implications. In this review, we discuss how TF interacts with other cell-surface proteins, which affect biological functions such as cell migration and cell survival. A vast number of publications have demonstrated the importance of TF-induced activation of protease-activated receptors, but recently published research has indicated a more complicated picture. As it has been discovered that TF interacts with integrins and receptor tyrosine kinases, novel signaling mechanisms for the TF/FVIIa complex have been presented. The knowledge of these new aspects of TF signaling may, for instance, facilitate the development of new treatment strategies for cancer and acute coronary syndromes, two examples of diseases characterized by aberrant TF expression and signaling.
Keywords: tissue factor; factor VIIa; intracellular signaling; cell migration; apoptosis